INTERELASI DAN INTERAKSI KAWASAN KAMPUS PERGURUAN TINGGI DI KOTA YOGYAKARTA - Sumarjo H (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2005)
ABSTRACTThe purpose of this research is to find a theory model of interrelationshiptheory between campus region with its environment, and the interaction betweencampus group that located in the city with other group that located in the urbanfringe of Yogyakarta.The sampling of this research has taken purposively, campus group thatlocated in the city consist of UGM, UNY, USD 1, UAJ and UII 1. Other group thatlocated in the urban fringe represented by UPN, STIE, U1I2, USD 2 and STIPER.Analisys of the data that already taken has decided to use quantitative method.The result of this research indicates there are significant interrelationshipbetween campus region with its environment, with relationship frequency 74%and 80%. The interaction between campus group that located in the city withother group that located in the urban fringe of Yogyakarta seem equal, so it canbe concluded that the relationship formed in concentric pattern.Keywords: interrelation, interaction, campus region